REKONSTRUKSI KONSEP KAFA’AH DALAM PERKAWINAN ADAT MINANGKABAU: ANALISIS MAQASID AL-SYARIAH - Vicky Aprilian; Muhammad Yassir (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the concept of kafa'ah in Islamic jurisprudence and its relevance to marriage compatibility practices in Minangkabau society through the perspective of maqasid al-shari'ah. The research employs a qualitative approach through field research in Batusangkar conducted in November-December 2025. Data were collected through in-depth interviews with 12 informants consisting of ninik mamak (traditional elders), religious leaders, married couples, and local academics, then analyzed descriptively-qualitatively using a thematic approach. Results indicate that all respondents (100%) prioritize religion and morals as the primary compatibility criteria, followed by economy (91.7%), lineage and ethnicity (83.3%), mental readiness (58.3%), and education (58.3%). These findings demonstrate strong compatibility between the concept of kafa'ah in Islamic jurisprudence and Minangkabau customary practices. Maqasid al-shari'ah analysis reveals that Minangkabau compatibility practices reflect efforts to preserve the five fundamental objectives of shari'ah: hifz al-din, hifz al-nafs, hifz al-'aql, hifz al-nasl, and hifz al-mal. The philosophy "Adat basandi syarak, syarak basandi Kitabullah" proves to be not merely a slogan but a principle genuinely manifested in partner selection practices, despite shifts in customary values such as weakening ninik mamak authority and reduced emphasis on lineage factors.